Glutamate excitotoxicity in neurons triggers mitochondrial and endoplasmic reticulum accumulation of Parkin, and, in the presence of N-acetyl cysteine, mitophagy - Victor S. Van Laar (Neurobiology of Disease, 2015)
Disruption of the dynamic properties of mitochondria (fission, fusion, transport, degradation, and biogenesis) has been implicated in the pathogenesis of neurodegenerative disorders, including Parkinson's disease (PD). Parkin, the product of gene PARK2 whose mutation causes familial PD, has been linked to mitochondrial quality control via its role in regulating mitochondrial dynamics, including mitochondrial degradation via mitophagy. Models using mitochondrial stressors in numerous cell types have elucidated a PINK1-dependent pathway whereby Parkin accumulates on damaged mitochondria and targets them for mitophagy. However, the role Parkin plays in regulating mitochondrial homeostasis specifically in neurons has been less clear. We examined whether a stressor linked to neurodegeneration, glutamate excitotoxicity, elicits Parkin–mitochondrial translocation and mitophagy in neurons. We found that brief, acute exposure to glutamate causes Parkin translocation to mitochondria in neurons, in a calcium- and N-methyl-d-aspartate (NMDA) receptor-dependent manner. In addition, we found that Parkin accumulates on endoplasmic reticulum (ER) and mitochondrial/ER junctions following excitotoxicity, supporting a role for Parkin in mitochondrial–ER crosstalk in mitochondrial homeostasis. Despite significant Parkin–mitochondria translocation, however, we did not observe mitophagy under these conditions. To further investigate, we examined the role of glutamate-induced oxidative stress in Parkin–mitochondria accumulation. Unexpectedly, we found that glutamate-induced accumulation of Parkin on mitochondria was promoted by the antioxidant N-acetyl cysteine (NAC), and that co-treatment with NAC facilitated Parkin-associated mitophagy. These results suggest the possibility that mitochondrial depolarization and oxidative damage may have distinct pathways associated with Parkin function in neurons, which may be critical in understanding the role of Parkin in neurodegeneration.